(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study analyzes the romantic formula in Midnight Sun (2018) by analyzing the plot and characterization through the lens of John G. Cawelti’s romantic formula theory, supported by Radway’s theory. Using a qualitative research design and an objective literary criticism approach, this study identifies the key elements of the romantic formula, including the initial meeting between the protagonists, the development of their relationship, the introduction of conflict, and its resolution. The findings show that Midnight Sun successfully applies the classic structure of romantic narratives. The film follows Cawelti’s stages from the first meeting, the development of the relationship, emotional conflict, and ends with a bittersweet yet meaningful resolution. The characterization revealed by Radway reflects the romantic formula that provides emotional depth and satisfaction for the audience. The findings show that Midnight Sun follows the common romantic structure, where the relationship between the hero and heroine develops through emotional and situational obstacles before reaching a resolution. This study contributes to the broader discourse on romantic narratives in popular cinema, offering insights into the application of formulaic storytelling in contemporary films.